Hubungan Harga Kopi di Indonesia dengan Negara Eksportir Utama dan Importir Utama: Pendekatan Kointegrasi dan Koreksi Kesalahan - Purwadi Purwadi; Sri Widodo; Masyhuri Masyhuri; Djuwari Djuwari (Jurnal Dinamika Sosial Ekonomi, 2004)
This paper examines relationships between Indonesia with major exporters and major importers coffee prices: Cointegration and Error Correction Approach. The use of error correction model is appropriate because all price that analysis are first-differenced stationary and cointegrated. The result suggest that coffee prices in Indonesia respond to restore equilibrium relationship with coffe prices in Brasil, Vietnam and USA, Germany, Japan, while all of there do not respond to restore equilibria would suggest that Indonesia is price leadership. The implication that's Indonesia can to play the role for stimulate to promote rising coffee prices in world market at the next time.Keywords: major exporters, major importers, Cointegration and Error Correction Approach